Penentuan Cadangan Premi Asuransi Jiwa Dengan Metode Fackler - Faturachman, Faturachman; Suyitno, Suyitno; Rizki, Nanda Arista (EKSPONENSIAL, 2022)
Insurance is an agreement between two parties, where one party is obliged to pay and the other party has the obligation to provide compensation to the premium payer if something happens to the party in accordance with the agreement that has been made. The main problem faced by insurance companies is that the fees paid through premiums are not sufficient to finance compensation payments at the beginning of the policys, To overcome the shortage of costs the insurance company must have a reserve fund called a premium reserve. The purpose of this study was to determine the reserve for term, endowment and whole life insurance premiums using the Fackler method. The variables used in this study are the customer's age, gender, payment term, interest rate and the sum insured. In this study, premium reserves were calculated for participants aged 30 years, men and women, with a payment term of 30 years, an interest rate of 6.75%, and an insurance value of Rp. 100,000,000. Based on the calculation results, the reserve value of term life insurance premium for customers with 30 years of age and the insurance period of 30 years increases at the beginning of the year to the 21st year, after which it decreases until the reserve at the end of the 30th year, the value of the lifetime insurance premium reserve. life for customers with 30 years of age always increases from the beginning of the year to the last year where the payment for male customers is Rp. 93,176,962 and women in the amount of Rp. 93,296,217,156250. The reserve value of dual-purpose life insurance premiums for customers with 30 years of age and insurance period of 30 years always increases from the beginning of the year to the end of the year of payment of Rp. 100,000,000. The large difference in premium reserves for men and women is due to the higher chance of life for women than men.